Effectiveness of Telehealth in Improving Quality of Life and Lowering Depression in Post-Stroke Patients: A Meta-Analysis - Siti Luluk Khamidahtun Ni'mah; Didik Tamtomo; Bhisma Murti (Journal of Epidemiology and Public Health, 2023)
Background: People who have a stroke are generally more likely to have difficulty managing daily activities such as walking, bathing, dressing, and participating in activities in the community and showing symptoms of depression that affects the quality of life. Telehealth is here to help people communicate with health workers without having to come directly to health facilities. The study aims to analyze how much effect telehealth has in improving the quality of life and reducing the risk of depression in post-stroke patients.Subjects and Method: This was a meta-analysis study using PICO. Population: post-stroke patients. Intervention: telehealth. Comparison: no telehealth. Outcome: quality of Life and depression. This study used articles from several databases namely Pubmed, Google Scholar, Science Direct, and Cochrane Library using the keywords "Stroke" AND "telehealth" OR "Telerehabilitation" OR "Tele-medicine" OR "Mobile health" OR "mHealth " OR "eHealth" AND "Quality of Life" OR "Health-Related Quality of Life" AND "Depression" AND "Randomized Controlled Trial" OR "RCT" to identify relevant studies. The articles included in the study were articles in English with RCT study design, published between 2012 and 2022. Steps in the systematic review were carried out based on guidelines from PRISMA flow diagram. Quantitative analysis was performed using Revman 5.3.Results: 8 RCTs article from America, Asia, and Europe showed that post-stroke patients who obtained telehealth services on average had 0.87 units higher quality of life than those without telehealth (SMD=0.87; 95% CI =0.30 to 1.44; p=0.003). 8 RCTs article from America and Europe showed that post-stroke patients who obtained telehealth services on average had 0.44 units lower depression than those without telehealth (SMD= -0.44; 95% CI=-0.79 to -0.09; p= 0.010).Conclusion: Telehealth can improve quality of life and lower the risk of depression in post-stroke patients. Keywords: telehealth, post-stroke, quality of life, depression Correspondence:Siti Luluk Khamidahtun Ni'mah. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: lulupanma@gmail.com. Mobile: +628562563503.